Desalination of Seawater using Pahae Natural Zeolite-Activated Carbon derived from Kepok Banana Peel (Musa paradisiaca Linn.) - Susilawati; Nitsae, Merpiseldin; Sinuhaji, Perdinan; Irma, Mutia; Lubis, Hariyati; Rinaldi, Fajar; Rafly Ihsan As Siddiq, Muhammad (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
The escalating demand for freshwater due to increased global population and intensified industrial activities necessitates innovative approaches to water desalination. This study explores the efficacy of a novel composite adsorbent material consisting of Pahae natural zeolite and activated carbon derived from Kepok banana peels for seawater desalination. This research synthesizes and evaluates the composite under varying conditions to ascertain its potential as an effective adsorbent material. Characterization methods included scanning electron microscopy (SEM), energy dispersive X-ray (EDX), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Brunauer-Emmett-Teller (BET), and salinity removal measurement. The results demonstrated that the 85:15% zeolite to activated carbon ratio exhibited the highest porosity of 61.04% and a significant water absorption capacity of 86.65%. This composition also achieved the most substantial salinity reduction, lowering the initial salinity from 27.70‰ to 18.53‰ with a removal efficiency of 33.10%. SEM analyses revealed a more porous surface morphology at 85:15% which corroborated with the higher salinity removal efficiency. BET results indicated that the optimal pore size and distribution occurred in the 85:15% composition which directly correlated with enhanced adsorption capacities. This study reports the potential of using sustainable materials such as zeolite and agricultural waste-derived activated carbon for cost effective and environmentally friendly desalination processes. The findings suggest that such composites can be tailored to improve performance and provide a viable solution to the global freshwater scarcity challenge.